Implementasi Kepmenpanrb No. 347 Tentang Pengadaan PPPK Tahun 2024 Di Ruang Lingkup Dispora Provinsi Kalimantan Tengah - Fery; Khairun; Dewi; Hafid; Raihan (Jurnal Ilmu Syariah dan Hukum (JISYAKU), 2025)
The Decree of the Minister of State Apparatus Utilization and Bureaucratic Reform (KepmenPANRB) Number 347 of 2024 was issued as the main technical instrument to realize the mandate of Law Number 20 of 2023 concerning the State Civil Apparatus (ASN Law), which requires the resolution of the status of non-ASN or contract (honorary) employees no later than December 2024. This research aims to analyze the implementation of KepmenPANRB 347/2024, particularly the procedural framework for the selection of Government Employees with a Work Agreement (PPPK), within the Youth and Sports Agency (DISPORA) of Central Kalimantan Province, as well as to identify and analyze structural gaps related to PPPK rights post-appointment. This study uses a juridical-normative and empirical-qualitative approach. Primary data was obtained through KepmenPANRB 347/2024 and the results of in-depth interviews with appointed PPPK at DISPORA Central Kalimantan. Data analysis was performed using George C. Edward III's Policy Implementation Model (Communication, Resources, Disposition, and Bureaucratic Structure). The research results indicate that DISPORA Central Kalimantan has successfully executed the non-ASN selection and structuring procedurally with high compliance. However, this procedural success is confronted by significant structural challenges post-appointment, especially regarding the rights gap in terms of pension guarantees and career paths that are not equivalent to Civil Servants (PNS), despite the workload being comparable. This structural inequality has the potential to reduce the work motivation of PPPK in the long term, although the positive disposition of regional leadership (the Governor of Central Kalimantan) serves as an important mitigating factor.